I know that by definition, a/(b/c)= a x 1(b/c)....but from there I am lost. Help please!
Well, I'm terrible at formal proofs, but consider:
multiply numerator and denominator by c, so that we get b by itself as the denominator (nobody likes pesky fractions in their denominator):
You can do this because c/c = 1.
now you have:
(c*a) / [c*(b/c)]
(c*a) / b
Nevermind I got it!
Ah, king you posted that just as I got it. Thanks though!
a/(b/c) = ac/b
Just a note that you have to be careful. The above is only true when both b and c are not 0. The reason is that division by 0 is undefined. In the above proof (c/c) is used which is 0/0 when c=0. 0/0 is undefined.
I just got shut out of physics thread by a Mentor poster who believed that:
ab = ac implies b = c for all values a. That is not correct when a is 0.
Separate names with a comma.